Computational investigation of the role of the iridium dihydrogen pincer complex in the formation of the cyclic pentamer (NH2BH2)(5) - Ghatak, Kamalika; Vanka, Kumar (Computational and Theoretical Chemistry, 2012)
Computational studies with density functional theory (DFT) and MP2 have been done to investigate the interaction between the iridium dihydrogen pincer complex: (POCOP)IrH2 (where POCOP = eta(3)-1,3(OPt-Bu-2)(2)C6H3) and NH2BH2, the immediate product of ammonia borane (NH3BH3) dehydrogenation. A mechanism has been proposed for an oligomerisation process at the metal centre that involves competition between (i) insertion of an NH2BH2 molecule into the (NH2BH2)(n) chain and (ii) termination of the chain leading to the formation of the cyclic (NH2BH2)(n) oligomer. The calculated Delta G values show that the competition favours insertion over termination for the cases n = 1 to n = 4 but favours termination for n = 5. The computational studies therefore indicate that the cyclic pentamer (NH2BH2)(5) would be formed during NH3BH3 dehydrogenation by the (POCOP)IrH2 catalyst, agreeing with experimental findings. The mechanistic understanding gained has implications for the facile regeneration of ammonia borane. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Ammonia borane; Hydrogen storage; Iridium pincer ligand catalyst; Mechanistic studies; Oligomerisation cycle

Exploring the potential of doped zero-dimensional cages for proton transfer in fuel cells: a computational study - Mane, Manoj V.; Venkatnathan, Arun; Ghatak, Kamalika; Vanka, Kumar (Journal of Physical Chemistry B, 2012)
Calculations with density functional theory (DFT) and MP2 have been done to investigate the potential of recently synthesized durable zero-dimensional (OD) nitrogen-based cage structures to perform as efficient proton-exchange membranes (PEMs) in fuel cells. Our calculations suggest that the hydrogenated 0-D cages, in combination with hydrogen-bonding 1,2,3- and 1,2,4-triazole molecules, would perform as highly efficient PEMs. The results are important in the context of the need for efficient PEMs for fuel cells, especially at higher temperatures (greater than 120 degrees C) where conventional water-based PEMs such as Nafion have been found to be ineffective.

Scandium-decorated MOF-5 as potential candidates for room-temperature hydrogen storage: a solution for the clustering problem in MOFs - Dixit, Mudit; Maark, Tuhina Adit; Ghatak, Kamalika; Ahuja, Rajiv; Pal, Sourav (Journal of Physical Chemistry C, 2012)
Transition-metal-based systems show promising binding energy for hydrogen storage but suffer from clustering problem. The effect of light transition metal (M = Sc, Ti) decoration, boron substitution on the hydrogen storage properties of MOF-5, and clustering problem of metals has been investigated using ab initio density, functional theory. Our results of solid-tate calculations reveal that whereas Ti clusters strongly Sc atoms do not suffer from this problem when decorating MOF-5. Boron substitution on metal-decorated MOF-5 enhances the interaction energy of both the metals with MOF-5. Sc-decorated MOF-5 shows a hydrogen storage capacity of 5.81 wt % with calculated binding energies of 20-40 kJ/mol, which ensures the room-teniperature applicability of this hydrogen storage material.

Metal or nonmetal cooperation with a phenyl group: route to catalysis? a computational investigation - Ghatak, Kamalika; Mane, Manoj; Vanka, Kumar (ACS Catalysis, 2013)
Full quantum mechanical calculations demonstrate that cooperativity in the form of the activation of the M-C bond (M: transition metal or boron, C: the ipso carbon of the coordinated phenyl group) can lead to effective catalysis pathways. Calculations show that the presence of an aromatic bidentate ligand attached to a transition metal, or even a main group element, such as boron, can lead to effective catalysts for,a, range of important reactions, such as the dehydrogenation of ammonia borane and formic acid and the activation of the N-H, bond in aromatic amities. Moreover, it is shown that the design of tridentate pincer complexes with the aromatic group at a terminal end can lead to effective M-C cooperativity. As such, the current work introduces a new concept in cooperativity and bond activation chemistry.
Keywords: catalysis; Density functional theory; metal-ligand cooperativity; small molecule activation

Computational investigation on the catalytic activity of Rh-6 and Rh4Ru2 clusters towards methanol activation - Ghatak, Kamalika; Sengupta, Turbasu; Krishnamurty, Sailaja; Pal, Sourav (Theoretical Chemistry Accounts, 2014)
Catalysis of molecular activation of small molecules through scission of strong chemical bonds is one of the major challenges faced by chemists. More specifically, activation of the strong C-H and O-H bonds of various alcohols, especially methanol, is one of the various important intermediate steps of key organic reactions. Our present work explores a suitable metal cluster catalyst towards methanol dissociation. In particular, we have examined the effect of ruthenium doping (Rh:Ru = 2:1) on the catalytic activity of Rh-6 cluster towards methanol dissociation. Density functional theory-based calculations illustrate two competitive pathways for methanol dissociation, which are via O-H and C-H bond breaking. Both the pathways are found to be energetically favourable in the presence of bimetallic and mono-metallic clusters. Importantly, energy barrier for O-H bond dissociation reduces considerably in doped cluster as compared to pure Rh-6 cluster and is smaller than the values reported for a number of other small metallic clusters.
Keywords: Bimetallic Clusters; Density Functional Theory (DFT); Doping; Methanol Activation; Rhodium Clusters